Web-Based System for Statistical Analysis and Thesis Progress Monitoring - Al Hadi, Ibadurrahman; Susilo, Edi (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2024)
Web-based monitoring systems serve as valuable tools in enhancing learning activities, particularly in the context of thesis supervision. Program heads and academic supervisors require timely, accurate information regarding students’ progress to guide academic outcomes effectively. This paper presents the development and implementation of an integrated web-based statistical and monitoring application tailored for thesis progress reporting. Built using the Laravel framework, the system incorporates statistical data visualization to enable students, supervisors, and administrators to interpret progress and communicate insights effectively. The system was developed using the prototype method, allowing iterative improvements based on user feedback. To ensure quality and functionality, the system was evaluated using the ISO/IEC 25010 quality model. A case study conducted in an electrical engineering department at a public university in Indonesia, involving students, academic supervisors, and administrative staff. The results demonstrate that the system not only improves oversight and coordination but also supports data-driven decision-making. By offering a clear, accessible overview of thesis progress, the application empowers all parties to take timely corrective actions, ultimately enhancing the overall educational experience.